Dieten hos barn och vuxna i Westerhus: Data från spårämnen, kolisotoper och odontologi - Iregren, Elisabeth; Jungner, Högne; Räisänen, Jyrki; Alexandersen, Verner (Hikuin, 2000)
The diet for adults and children at Westerhus. Data from trace element and carbon isotope analyses and odontology By Elisabeth Iregren, Högne Jungner, Jyrki Räisänen and Verner Alexandersen The individuals from Westerhus were randomly selected to cover all age groups and both sexes. Bone samples were taken from 94 skeletons (25%) of the population. Different skeletal elements have been used in the PIXE (Proton Induced X-ray Emission) analyses. The following elements were studied: Ca (calcium), the earth metals Mn (manganese) and Fe (iron); the trace elements Zn (zinc), Sr (strontium) and Cr (chromium); the heavy metal Pb (lead) and further Cu (copper), Br (bromine), Ni (nickel), Mo (molybdenum), Zr (zirconium). Soil samples were examined as well as several bone samples of a few individuals. In Westerhus no severe influence of heavy metals has been traced. Lead is found in small amounts in the skeletons. Compared to other medieval people the values of zink indicate a low intake of animal protein in the Westerhus population. Copper is also found in very low amounts. This proves that they did not consume any marine food at all. When using the definitions by Johansen et al. (1986) for evaluating the values of the carbon isotopes, we may conclude that the individuals were presumably consumers of mainly terrestrial food. Thus, the data on carbon isotopes, zinc, and copper verify one another. Results on the Sr/Ca in the diet and the bearing on weaning are presented. It is highly likely that most children in Westerhus were given human milk until the age of 2 years. Single individuals show, however, signs of enamel hypoplasia, which indicates that a few children were given supplementary food earlier. Above the age of two the variation between individuals increases, hinting to different feeding practices in different families. We believe that some children were not weaned until the age of 3-4 years, but above the age of 5 the children show Sr/Ca-values similar to the adults. Swärdstedt (1966) studied adults and found that the number of enamel hypoplasia increased markedly in Westerhus during the years 2.5-4. Evidently, this period in life was critical even to those who survived infancy.